Peran Analgesik Nonsteroidal Anti-inflammatory Drugs (NSAIDs) dan Analgesik Non-NSAIDs dalam Penanganan Nyeri - Jan S. Purba (PT Dexa Medica, 2022)
Pain is an unpleasant sensory and emotional experience associated with actual or potential tissue damage, or described in terms of such damage. The experience of pain serves as one of the most important protective mechanisms of the body. Understanding the mechanisms of pain is important for any clinician since chronic pain is a global problem that transcends all medical specialties. Chronic pain describes pain that persists or progresses over a long period of time. In contrast to acute pain that arises suddenly in response to a specific injury and is usually treatable, chronic pain persists over time and is often resistant to medical treatments. There are a variety of treatment options for people with chronic pain. The goal of pain management is to provide symptom relief and improve an individual's level of functioning in daily activities. A number of types of medications have been used in the management of chronic pain.